2008
DOI: 10.1016/j.jallcom.2006.10.155
|View full text |Cite
|
Sign up to set email alerts
|

Structural study of metastable tetragonal YSZ powders produced via a sol–gel route

Abstract: Sol-gel yttria stabilized zirconia (YSZ) is investigated in this paper. The final aim is to process YSZ powders into stable slurries in order to prepare thick coatings for thermal barrier to be applied on hot turboengine components. In fact, this system is well-known for its excellent thermomechanical resistance at elevated temperatures but the relationship between these performances and the structural and microstructural characteristics of these materials is not fully understood. This paper reports a prelimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
83
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(103 citation statements)
references
References 17 publications
(27 reference statements)
16
83
1
3
Order By: Relevance
“…It means that the nature of the bonds in the crystalline lattice were similar but changes in the local symmetry must exist. As addressed in previous works a shift of the Raman band toward higher wavelength represents an increment of the oxygen displacement, i.e a lower stabilisation of the tetragonal phase because of a decreasing in the amount of stabilizer ions (Y 3+ ) [26]. It agrees with the EDX analysis so that in coatings chemically attacked with CMAS, especially CMAS-2, a lixiviation of yttrium cations observed gave rise to a lower tetragonality in zirconia phase.…”
Section: Study Of the Crystalline Phases By Ramansupporting
confidence: 88%
“…It means that the nature of the bonds in the crystalline lattice were similar but changes in the local symmetry must exist. As addressed in previous works a shift of the Raman band toward higher wavelength represents an increment of the oxygen displacement, i.e a lower stabilisation of the tetragonal phase because of a decreasing in the amount of stabilizer ions (Y 3+ ) [26]. It agrees with the EDX analysis so that in coatings chemically attacked with CMAS, especially CMAS-2, a lixiviation of yttrium cations observed gave rise to a lower tetragonality in zirconia phase.…”
Section: Study Of the Crystalline Phases By Ramansupporting
confidence: 88%
“…According to the lattice parameter results, the ratio c /a √ 2 for the tetragonal phase falls into the range of 1.010 to 1.000. This indicates that the tetragonal phase in the as-sprayed coating is non-transformable [39]. After thermal cycling, no monoclinic phase was detected from the XRD patterns and the tetragonal phase was non-transformable; but a cubic phase was detected from both thermally-cycled Samples M and N. According to quantitative analysis, the amount of cubic phase in the both coatings is around 12 wt %.…”
Section: Thermal Cycling Performance Of the Coatingsmentioning
confidence: 91%
“…4). Viazzi et al [21] showed, after Ref. [27], the lattice parameters for the tetragonal (t ) phase, as functions of yttria content (YO 1.5 in mol%) x:…”
Section: Tetragonal Phasementioning
confidence: 99%
“…The crystallite size was about 11 nm for the t phase and about 8 nm for the t phase. Viazzi et al [21] have studied the structure of metastable tetragonal YSZ powders produced via a sol-gel route. The samples were studied as a function of yttria content and annealing temperatures up to 1400…”
Section: Introductionmentioning
confidence: 99%